Calving trend in mithun - PERUMAL, P; KUMAR, BRIJESH; RAJKHOWA, C (The Indian Journal of Animal Sciences, 2014)
The present retrospective study was conducted to assess the calving trend in mithun in semi – intensive. The calving data were collected from 2002 to 2012 from the calving register of mithun farm. The data were analysed month- wise, season-wise and sex ratio in month wise. Results revealed that highest birth rate was at September followed by December and January and lowest in May and June. Maximum calving rate was in winter and lowest was in summer. Highest percentage of male calf was born in August and October (71.42%) and lowest in December (27.27%), whereas highest percentage of female calf was born in December (72.73%) and lowest in August and October (28.58%). The result of calving trend at mithun farm, compel us to speculate that some sort of seasonality do exist in mithuns.